2007
DOI: 10.1017/s0959270907000858
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the illegal parrot trade in Santa Cruz de la Sierra, Bolivia, with emphasis on threatened species

Abstract: SummaryWe monitored the illegal pet trade in Los Pozos pet market from August 2004 to July 2005. As indicated in Bolivian law, all unauthorized trade in wild animal species is illegal, especially species considered threatened by IUCN. During this period, we recorded 7,279 individuals of 31 parrot species, including four threatened species, two of which were being transported from Brazil through Bolivia to markets in Peru. The most frequently sold species was the Blue-fronted Parrot Amazona aestiva with 1,468 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 0 publications
2
58
0
1
Order By: Relevance
“…For example, wildlife seizures made at entry points in Asia (Nijman 2010), the EU (van Uhm 2016), and the US (Kurland and Pires 2017;Petrossian et al 2016) have found that certain taxonomic groups of wildlife are disproportionately trafficked into major demand markets while others are rarely seized. At the local level, market surveys commonly find particular species disproportionately sold in illicit markets (Gastanaga et al 2011;Herrera and Hennessey 2007;Lee et al 2005;Phelps and Webb 2015;Regueira and Bernard 2012) and field research has found certain wildlife is preferred for bushmeat by poachers (Holmern et al 2007). …”
Section: Crime Concentration: Does Illegal Wildlife Poaching and Tradmentioning
confidence: 99%
“…For example, wildlife seizures made at entry points in Asia (Nijman 2010), the EU (van Uhm 2016), and the US (Kurland and Pires 2017;Petrossian et al 2016) have found that certain taxonomic groups of wildlife are disproportionately trafficked into major demand markets while others are rarely seized. At the local level, market surveys commonly find particular species disproportionately sold in illicit markets (Gastanaga et al 2011;Herrera and Hennessey 2007;Lee et al 2005;Phelps and Webb 2015;Regueira and Bernard 2012) and field research has found certain wildlife is preferred for bushmeat by poachers (Holmern et al 2007). …”
Section: Crime Concentration: Does Illegal Wildlife Poaching and Tradmentioning
confidence: 99%
“…Ejemplo de ello fue la extinción del endémico guacamayo cubano Ara cubensis, por el comercio hacia España, y la pérdida de hábitat . Por ejemplo, en Santa Cruz de la Sierra, Bolivia, se proyecta un mercado de 22 000 loros/año (Herrera & Hennessey, 2007). En México, se estima una tasa de captura de 65 000-78 500 psitácidos/año (Cantú, Sánchez, Grosselet, & Silva, 2007).…”
Section: Discussionunclassified
“…Many of the people in these regions like the products that come from these species (e.g. tiger skins, elephant ivory) or in the case of parrots, enjoy their company as household pets (Smith et al 2003;Project Tiger 2005;Cantu et al 2007;Herrera and Hennessey 2007;Lemieux and Clarke 2009;The Economist 2008).…”
Section: Trade Bans and Regulating The Tradementioning
confidence: 99%
“…Recent evidence shows most of the illegal parrot trade is fuelled by internal markets within neo-tropical countries and not international markets as popular opinion suggests. For example, illicit pet market research in Peru and Bolivia as well as interviews with parrot trappers in Mexico reveals tens of thousands of parrots are annually poached in each country for local and regional demand (Cantu et al 2007;Herrera and Hennessey 2007;Gastanaga et al 2010).…”
Section: The Illegal Parrot Tradementioning
confidence: 99%
See 1 more Smart Citation